Incomplete release indications in surgical treatment of congenital pes equinovarus - Karakurt, Lokman; Yılmaz, Erhan; İnci, Murat; Serin, Erhan; Belhan, Oktay (Fırat University, 2002)
Aim: The aim of this study was to discuss the incomplete release in congenital pes equinovarus of problematic foot was a good choose or not. Material and Methods: One case had bilateral relapsed clubfoot deformity which operated previously. One case had congenital band syndrome and 1 had Epidermolysis Bullosa. For avoid the skin and circulatory problems, incomplete release technique was performed in all cases. Results: According to the Simons clinical and radiological criteria, 3 feet (75 %) were unsatisfactory and 1 feet (25 %) was satisfactory. According to the Napiontek's clinical criteria, 1 grade recovery was determined in all cases postoperatively. Conclusion: In the cases with skin and circulatory problems, incomplete release techniques may be used.

Amaç: Bu çalışmada, sorunlu ayaklarda konjenital pes ekinovarus (PEV) cerrahi tedavisinde inkomplet gevşetmenin iyi bir seçenek olup olmadığının tartışılması amaçlandı. Gereç ve Yöntem: Bir olgunun 2 ayağına önceden cerrahi yapılmış ve nüks mevcuttu. Bir olguda konjenital bant sendromu, 1 olguda da Epidermolizis Bülloza mevcuttu. Konjenital PEV'li bu 3 olgunun 4 ayağına cilt ve dolaşım sorunlarından kaçınmak için inkomplet gevşetme ameliyatı yaptık. Bulgular: Simons'un klinik ve radyolojik kriterlerine göre 3 ayakta (%75) başarısız, 1 ayakta (%25) başarılı sonuç bulduk. Napiontek'in klinik değerlendirme kriterlerine göre, tüm ayaklarda ameliyat sonrası 1 derece iyileşme saptandı. Sonuç: Cilt ve dolaşım sorunu olan olgularda komplet subtalar gevşetme yapılamıyorsa, inkomplet gevşetme yöntemleri tercih edilebilir.
Konjenital Pes Ekinovarus Cerrahi Tedavisinde İnkomplet Gevşetme Endikasyonları